2004
DOI: 10.1111/j.0022-202x.2004.23229.x
|View full text |Cite
|
Sign up to set email alerts
|

Nickel and DNCB Induce CCR7 Expression on Human Dendritic Cells Through Different Signalling Pathways: Role of TNF-α and MAPK

Abstract: After application of haptens on the skin, immature dendritic cells (DC), also named Langerhans cells (LC), migrate to the draining lymph node to sensitize naïve T-lymphocytes. Migration of DC involves many factors including the Cys-Cys chemokine receptor, CCR7. We investigated the effects of two well-known haptens, dinitrochlorobenzene (DNCB) and nickel (NiSO(4)), on the expression of CCR7 on human DC derived from CD34(+) progenitor cells. Both haptens were able to induce CCR7 expression and DC migration in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
80
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(91 citation statements)
references
References 47 publications
9
80
1
1
Order By: Relevance
“…Sensitizers have also been demonstrated to induce the expression of markers related to function and maturation of DCs, the production of proinflammatory cytokines, and the phosphorylation of members of the MAPK family and NF-kB pathway, thus mimicking the effects of danger signals (9)(10)(11)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensitizers have also been demonstrated to induce the expression of markers related to function and maturation of DCs, the production of proinflammatory cytokines, and the phosphorylation of members of the MAPK family and NF-kB pathway, thus mimicking the effects of danger signals (9)(10)(11)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…During the sensitization phase, skin dendritic cells (DCs) capture the metal bound to self-protein, migrate through the lymphatic vessels, and present the haptenprotein complex to naive T cells in the draining lymph node (7,8). Moreover, using human in vitro DC models, several groups have showed that chemical sensitizer treatment can induce phenotypic modifications with HLA-DR, CD86, CD40, CD83, and CCR7 upregulation and IL-12 and IL-8 production (9)(10)(11)(12).…”
mentioning
confidence: 99%
“…As immature DC, following induction of maturation after stimulation by inflammatory cytokines or haptens, up-regulate CCR7 [39,41,42], our next question was whether or not the expression of CCR7 on LC is impaired during the maturational changes following hapten application to SHPS-1 mutant mice. We found that expression of CCR7 on LC is suppressed following DNFB application in SHPS-1 mutant mice.…”
Section: Discussionmentioning
confidence: 99%
“…In human CD34 + -derived DC, nickel activates p38 MAPK, ERK1/2 and JNK, all of which are MAPKs involved in the expression of CD83, CD86 and CCR7 but not in the nickel-induced down-regulation of E-cadherin and Langerin (Boisleve et al, 2005). TNF-α production induced by DNCB was also linked to the activation of p38 MAPK and JNK (Boisleve et al, 2004). In previous results performed with the foetal skin-derived dendritic cell line (FSDC), we reported that DNFB activates p38 MAPK and ERK1/2 via the production of reactive oxygen species and that protein oxidation plays an important role in MAPKs activation (Matos et al, 2005b).…”
Section: Activation Of the Mitogen-activated Protein Kinases (Mapks)mentioning
confidence: 92%